2020
DOI: 10.1007/s11625-020-00793-y
|View full text |Cite
|
Sign up to set email alerts
|

Storylines for practice: a visual storytelling approach to strengthen the science-practice interface

Abstract: A growing number of scientific publications is available to promote sustainable river management. However, these publications target researchers rather than water management professionals who are responsible for the implementation of management practices. To bridge this science-to-practice gap, we conceptualize and propose a series of steps to prepare effective storylines targeted at a practitioner audience. We developed this approach within a research program that supports integrated and collaborative river m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Stakeholders are increasingly incorporated in research through collaborations between scientists, companies and governments, often stimulated by funding agencies. For example, Cortes Arevalo et al (2020) use visual storytelling to strengthen the sciencepractice interface. Additionally, working groups that stimulate the bridge between science and practice have also been set up, such as the IAHS CANDHY working group.…”
Section: Bridging Science and Practicementioning
confidence: 99%
“…Stakeholders are increasingly incorporated in research through collaborations between scientists, companies and governments, often stimulated by funding agencies. For example, Cortes Arevalo et al (2020) use visual storytelling to strengthen the sciencepractice interface. Additionally, working groups that stimulate the bridge between science and practice have also been set up, such as the IAHS CANDHY working group.…”
Section: Bridging Science and Practicementioning
confidence: 99%
“…By interacting with the physical board, players—regardless of background and expertise—can collaboratively explore river interventions while the computational models provide feedback on the impact of players' actions into the costs, biodiversity and flood safety indicators (den Haan et al, 2020). An important element of the online knowledge base are storylines that translate research results in an interactive way for actors in the formal policy space and the stakeholder space (Cortes Arevalo et al, 2020).…”
Section: Transdisciplinary Approaches Of the Selected Projectsmentioning
confidence: 99%
“…Many have recognised storytelling as part of wider efforts at decolonising research methodologies and epistemologies (for example, Datta, 2018;Geia et al, 2013;Pualani Louis, 2007;Rieger et al, 2021), including in the digital realm (Cunsolo Willox et al, 2012). On the public engagement side, diverse accounts, especially from the natural sciences, detail using stories to promote engagement with science (for example, Bordenave, 2018;Cortes Arevalo et al, 2020;ElShafie, 2018;Olson, 2015). A post-event case study at National Museum Indonesia concluded that storytelling helps secure public and cultural engagement (Soerjoatmodjo, 2015).…”
Section: Research Storytelling and Public Engagementmentioning
confidence: 99%